Exploring Professional Agency in Domestic Violence Interventions Within Social and Health Care - Piippo, Sisko (Nordic Journal of Working Life Studies, 2025)
While the existing research on domestic violence (DV) interventions has provided substantial insights into the challenges associated with addressing DV, the factors that facilitate its intervention in social and health care remain under-researched. This study focuses on DV intervention practices that professionals have deemed successful and employs subject-centered sociocultural theories of professional agency to analyze how professional agency is manifested in these situations. To this end, 10 focus group interviews were conducted with 45 experienced social and health care professionals. The collected data were subjected to thematic content analysis. The findings illustrate how professional agency is manifested in various contexts: through understanding DV as a phenomenon and its contextual factors (epistemic agency), launching a process (processual agency), collaborating with other professionals (relational agency), and reflecting on one’s own actions and emotions (reflective agency).